A route optimization algorithm and its application to mobile location management in ATM networks. - Dommety, G. (IEEE Journal on selected areas in communications)
In this paper, we propose an algorithm for optimizing the route of a connection that becomes suboptimal due to operations such as handoffs and location-based reroutes, for mobile ATM (asynchronous transfer mode) networks based on the PNNI (private network-to-network interface) standard. This algorithm uses hierarchical route information of the connection and summarized topology and loading information of the network to determine a ?crossover node? such that adjusting the connection from that crossover node results in an optimally routed connection. We then apply this algorithm to the mobile location management problem. Location management schemes have been proposed in which an incoming call to a mobile is first routed to its home switch (based on summarized reachability data) and then rerouted to the mobile's current location. If we consider such rerouting a ?first phase? of mobile connection setup, a ?second phase? is required to optimize the paths of such rerouted connections. Such an approach is considered a two-phase mobile location/connection setup scheme. Alternatively, an incoming call to a mobile can be first routed to its home switch based on summarized reachability data, and then ?cranked back? to an optimal crossover node before rerouting the connection to the mobile's current location. Such a scheme is a one-phase mobile location/connection setup scheme since it directly results in an optimal path. A comparative performance analysis of the one- and two-phase connection setup schemes is presented. Measures of comparison are call setup delay and the amount of network resources allocated to a connection. The maximum call setup delay (worst case call setup delay) is lower in the two-phase scheme, but the average call setup delay is lower in the one-phase scheme. The amount of resources required for a connection in the two-phase scheme (prior to route optimization) is significantly greater than that in the one-phase scheme